1992
DOI: 10.1111/j.1365-2923.1992.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of problem-based learning in Jiujiang Medical College: why not try it?

Abstract: Against a background of problems in delivering rural health care in the Jiujiang district of China, this paper outlines the development of a relevant 3-year SSO (Strengthening the training of clinical skills, Strengthening preventive medicine education, and Optimizing curricular structure) programme at Jiujiang Medical College (JMC). Some comparisons between JMC and the Southern Illinois University School of Medicine (SIUSM) are made, and the possibility of applying problem-based learning to JMC is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Andersen (1990, as above), Yang and Zhang (1991) and VanLeit (1995) suggested that clinical reasoning skills were gained through PBL and that through this method of learning the development of these skills was made more explicit to the students. In terms of research, there still appears to be little evidence to demonstrate that this is so.…”
Section: Critical Analysesmentioning
confidence: 97%
“…Andersen (1990, as above), Yang and Zhang (1991) and VanLeit (1995) suggested that clinical reasoning skills were gained through PBL and that through this method of learning the development of these skills was made more explicit to the students. In terms of research, there still appears to be little evidence to demonstrate that this is so.…”
Section: Critical Analysesmentioning
confidence: 97%
“…There has been a far‐reaching interest in PBL within the health professions and it has become an accredited approach in many medical schools worldwide ( De Volder & De Grave, 1989; Walton & Mathews, 1989; Yang & Zhang, 1991; Des Marchais et al , 1992 ; Hill, 1992; Thomas, 1992; de Boo, 1996). However, nursing schools are also now recognizing the value of having a PBL curriculum; this is illustrated by the increasing numbers adopting the process around the world, particularly in Wales ( Andrews & Jones, 1996; Biley & Smith, 1998a, 1998b; Biley, 1998), Sweden ( Foldevi, 1995), Australia ( Ryan et al , 1992 ; Creedy & Hand, 1994), Canada ( Rideout, 1994), and elsewhere.…”
Section: A Panoramic Lensmentioning
confidence: 99%